Blood free-circulating DNA testing by highly sensitive methylation assay to diagnose colorectal neoplasias - Suehiro, Yutaka (Oncotarget, 2018)
Although methylated TWIST1 is a biomarker of colorectal neoplasia, its detection from serum samples is very difficult by conventional bisulfite-based methylation assays. Therefore, we have developed a new methylation assay that enables counting of even one copy of a methylated gene in a small DNA sample amount without DNA bisulfite treatment. We performed this study to evaluate the sensitivity and specificity of serum DNA testing by the new methylation assay in combination with and without the fecal immunochemical test for hemoglobin for the detection of colorectal neoplasia. This study comprised 113 patients with colorectal neoplasia and 25 control individuals. For the new methylation assay, DNA was treated in two stages with methylation-sensitive restriction enzymes, followed by measurement of copy numbers of hTERT and methylated TWIST1 by multiplex droplet digital PCR. The fecal immunochemical test had a sensitivity of 8.0% for non-advanced adenoma, 24.3% for advanced adenoma, and 44.4% for colorectal cancer, and a specificity of 88.0%. The new assay had a sensitivity of 36.0% for non-advanced adenoma, 30.0% for advanced adenoma, and 44.4% for colorectal cancer, and a specificity of 92.0%. Combination of the both tests increased the sensitivity to 40.0%, 45.7%, and 72.2% for the detection of non-advanced adenoma, advanced adenoma, and colorectal cancer, respectively, and resulted in a specificity of 84.0%. Combination of both tests may provide an alternative screening strategy for colorectal neoplasia including potentially precancerous lesions and colorectal cancer.